Comparative Study of Clinical, Pathological, Radiological, and Genetic Features of Patients With Adult Ocular Adnexal Xanthogranulomatous Disease, Erdheim-Chester Disease, and IgG4-Related Disease of the Orbit/Ocular Adnexa - McKelvie, Penelope; McNab, Alan A; Hardy, Thomas; Rathi, Vivek (Ophthalmic plastic and reconstructive surgery, 2017)
To compare and contrast the clinical, radiologic, pathologic, and genetic features of patients with ocular adnexal IgG4-related disease (IgG4-RD) and patients with adult ocular adnexal xanthogranulomatous disease (XG). This retrospective review study identified patients with histological evidence of either disease from records of the pathology department of our hospital from 1996 to 2014. Clinical, imaging, and a variety of histopathologic features were collected for 23 patients with IgG4-RD and 13 patients with XG. Next generation sequencing with a 50-gene cancer screening panel was performed on biopsy tissues from 10 patients in each group. Statistical differences between the 2 groups include eyelid (67%; p = 0.0002) and anterior orbital (75%; p = 0.0352) predilection for XG except for Erdheim-Chester disease subgroup which was more posterior and diffuse. Eyelid involvement was rare (4%) for IgG4-RD. Involvement of orbital nerves was seen in 30% of IgG4-RD and 0% in XG (p = 0.0695). Five patients with IgG4-RD developed malignancy (4 lymphoma, 1 leiomyosarcoma), but none of XG patients. Discriminating pathological features were the presence of any IgG4+ plasma cells (p = 0.0121) and the ratio of IgG4+/IgG+ plasma cells (p =0.0294) for IgG4-RD. Five of 12 (42%) patients with XG had sufficient numbers of IgG4+ plasma cells/high power field to fulfill published diagnostic criteria for IgG4-RD, and 5 (42%) had a ratio of IgG4+/IgG+ plasma cells over 40%, but the numbers overall were less than seen in the IgG4-RD patients. The only genetic difference between the 2 groups was that BRAF V600E mutation was found in 1 of the 2 Erdheim-Chester disease patients, which form a subgroup of XG. IgG4-RD and XG share clinical, imaging, and histopathological features including IgG4+ plasma cells. Significant differences were the eyelid involvement in XG, orbital nerve involvement, and an elevated IgG4+/IgG+ ratio in IgG4-RD and the only genetic abnormality found was BRAF V600E mutation in the Erdheim-Chester disease subgroup of XG.